Sintering Behavior of a Six-Oxide Silicate Bioactive Glass for Scaffold Manufacturing - Elisa Fiume; Gianpaolo Serino; Cristina Bignardi; Enrica Verné; Francesco Baino (Applied Sciences, 2020)
The intrinsic brittleness of bioactive glasses (BGs) is one of the main barriers to the widespread use of three-dimensional porous BG-derived bone grafts (scaffolds) in clinical practice. Among all the available strategies for improving the mechanical properties of BG-based scaffolds, strut densification upon sintering treatments at high temperatures represents a relatively easy approach, but its implementation might lead to undesired and poorly predictable decrease in porosity, mass transport properties and bioactivity resulting from densification and devitrification phenomena occurring in the material upon heating. The aim of the present work was to investigate the sinter-crystallization of a highly bioactive SiO2-P2O5-CaO–MgO–Na2O–K2O glass (47.5B composition) in reference to its suitability for the fabrication of bonelike foams. The thermal behavior of 47.5B glass particles was investigated upon sintering at different temperatures in the range of 600–850 °C by means of combined thermal analyses (differential thermal analysis (DTA) and hot-stage microscopy (HSM)). Then, XRD measurements were carried out to identify crystalline phases developed upon sintering. Finally, porous scaffolds were produced by a foam replica method in order to evaluate the effect of the sintering temperature on the mechanical properties under compression loading conditions. Assessing a relationship between mechanical properties and sintering temperature, or in other words between scaffold performance and fabrication process, is a key step towards the rationale design of optimized scaffolds for tissue repair.